Germline and somatic vitelline proteins colocalize in aggregates in the follicular epithelium of Drosophila ovaries - Furriols, Marc (Landes Bioscience, 2014)
Nasrat and Polehole, two Drosophila proteins related functionally and by sequence, are secreted from the oocyte and incorporated into the vitelline membrane, where they play a role in the integrity of the same and in the activation of embryonic Torso RTK. In addition, they also accumulate in a punctate pattern in the follicular epithelium. Here we show that their accumulation at the follicle cells depends on their gene expression in the germline, indicating that these proteins move from the oocyte to the follicle cells in a process that does not require endocytosis. Finally we used cell markers to examine the distribution of these proteins at the follicle cells and show they accumulated in aggregates with vitelline membrane proteins in close association with the plasmatic membrane. We propose that these aggregates represent spatially restricted sinks for vitelline membrane proteins that fail to be incorporated into vitelline bodies and later on into the vitelline membrane.